Aetiology and risks factors associated with the fatal outcomes of childhood pneumonia among hospitalised children in the Philippines from 2008 to 2016: a case series study. Issue 3 (30th March 2019) - Dembele, Bindongo Price Polycarpe; Kamigaki, Taro; Dapat, Clyde; Tamaki, Raita; Saito, Mariko; Saito, Mayuko; Okamoto, Michiko; Igoy, Mary Ann U; Mercado, Edelwisa Segubre; Mondoy, Melisa; Tallo, Veronica L; Lupisan, Socorro P; et al.
Abstract : Objective: Pneumonia remains the leading cause of hospitalisations and deaths among children aged <5 years. Diverse respiratory pathogens cause acute respiratory infections, including pneumonia. Here, we analysed viral and bacterial pathogens and risk factors associated with death of hospitalised children. Design: A 9-year case series study. Setting: Two secondary-care hospitals, one tertiary-care hospital and one research centre in the Philippines. Participants: 5054 children aged <5 years hospitalised with severe pneumonia. Methods: Nasopharyngeal swabs for virus identification, and venous blood samples for bacterial culture were collected. Demographic, clinical data and laboratory findings were collected at admission time. Logistic regression analyses were performed to identify the factors associated with death. Results: Of the enrolled patients, 57% (2876/5054) were males. The case fatality rate was 4.7% (238/5054), showing a decreasing trend during the study period (p<0.001). 55.0% of the patients who died were either moderately or severely underweight. Viruses were detected in 61.0% of the patients, with respiratory syncytial virus (27.0%) and rhinovirus (23.0%) being the most commonly detected viruses. In children aged 2–59 months, the risk factors significantly associated with death included age of 2–5 months, sensorial changes, severe malnutrition, grunting, central cyanosis, decreased breath sounds, tachypnoea, fever (≥38.5°C), saturation of peripheral oxygen <90%, infiltration, consolidation and pleural effusion on chest radiograph. Among the pathogens, adenovirus type 7, seasonal influenza A (H1N1) and positive blood culture for bacteria were significantly associated with death. Similar patterns were observed between the death cases and the aforementioned factors in children aged <2 months. Conclusion: Malnutrition was the most common factor associated with death and addressing this issue may decrease the case fatality rate. In addition, chest radiographic examination and oxygen saturation measurement should be promoted in all hospitalised patients with pneumonia as well as bacteria detection to identify patients who are at risk of death.